A Prospective Randomized Comparative Clinical Trial to Analyze Pain and Surgical Outcomes Between Frontal Nerve Blocks and Subconjunctival Anesthesia for Conjunctival Mullerectomy Resection. Issue 6 (November 2018) - Zatezalo, Chad C.; Tavakoli, Mehdi; Ayala-Haedo, Juan; Callaway, Natalia F.; Ko, Marcus J.; Anagnostopoulos, Apostolos G.; Vanner, Elizabeth A.; Lee, Wendy W.
Abstract : Purpose: Conjunctival Müller's muscle resection (CMMR) is a posterior approach surgical technique to correct blepharoptosis. The purpose of this study is to compare patient-reported pain scores and surgical outcomes for patients who received 2 different anesthetic techniques during CMMR, frontal nerve block and subconjunctival injection. Methods: A prospective randomized comparative clinical trial enrolled 33 CMMR subjects from one tertiary eye center. Patients undergoing unilateral CMMR were randomized to receive either frontal nerve block or subconjunctival injection. For patients undergoing bilateral CMMR, each side was randomized to one of the injection techniques. Upper eyelid margin reflex distance was measured and recorded for each eye before and after surgery. Patients' pain scores were quantified using the Wong Baker Pain Scale. Subjects quantified their pain during, immediately after, 12 and 24 hours after surgery. Results: Twenty-four bilateral and 9 unilateral cases were enrolled in the study. Twenty-two (92%) subjects were female, and the mean patient age was 69 ± 12 years. The mean margin reflex distance was 1.1 mm preoperatively, which increased to 3.5 and 3.6 mm 2 months postoperatively in frontal nerve block and subconjunctival injection groups, respectively ( p value <0.0001). Both paired and nonpaired analyses demonstrated no significant difference in the pain score reported by the patients or the surgical outcomes between the 2 anesthesia techniques at any time during or after the surgery. There were no anesthetic-related complications. Conclusion: There was no statistically significant difference in pain scores or surgical outcomes in patients receiving frontal nerve block compared with those receiving subconjunctival injection during CMMR surgery. Abstract : Frontal nerve blocks and subconjunctival anesthesia for conjunctival mullerectomy resection ptosis surgery results in similar pain scores and surgical outcomes in a randomized clinical trial.